Competitiveness in Latin America: Ecuador case (Dimensión Empresarial, 2016)
The purpose of this paper is to show, from a bibliographical revision, the different approaches and policies regarding the Business Competitiveness presented in Latin America. Models and methodologies that are interesting because they show different views depending on culture, economy and perceptions of the situation in developing countries with similar cultures are included. In general, these studies cover the analysis and management elements such as profitability and Infrastructure Intangible Resources, Financial Information, Training Cooperation Networks, among others. On approaches to the Business Competitiveness in Ecuador, they showed the state's role in establishing policies and guidelines for strengthening the competitiveness of both public and private in different sectors of the Economy National Companies.
Keywords: Competitiveness; Competitiveness Models; Management